PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK MENGGUNAKAN APLIKASI CANVA PADA MATERI BILANGAN CACAH - Asmaryadi, Ahmad Ilham Asmaryadi; Estuhono, Estuhono; Akhadiah, Mely (Information Technology Education Department, 2024)
This research was motivated by the low understanding of the concept of the mathematics subject in class IV SD Negeri 189/II Sari Mulya due to the lack of use of learning media during teaching and learning activities. Efforts to overcome these problems require the development of comic learning media. This study aims to develop comic media as a learning medium and can be used in schools so that it can produce valid, practical, and effective learning media. This research is a type of development research that uses the PLOMP development model. This development goes through the stages of (preliminary research), (prototyping phase), (assessment phase). The research was conducted in class IV of SD Negeri 189/II Sari Mulya with 27 students. Data collection used the technique of filling out questionnaires from educators and students' responses as well as filling out student learning results sheets. Based on the results of the validation test from 3 validators, namely content, graphic and language validators, the average value was 86.54% with a very valid category. Practicality test results by practicing educators and students obtained an average value of 91.00% in the very practical category. The results of the effectiveness test in the form of a learning achievement test obtained from students obtained an average score of 98.46% in the very effective category.